Application experience of extracorporeal photopheresis for treatment of acute “graft-versus-host” disease after allogeneic hematopoietic stem cell transplantation - A. V. Kozlov; T. A. Bykova; I. I. Kulagina; S. N. Bondarenko; E. V. Semenova; l. S. Zubarovskaya; B. V. Afanasyev (Онкогематология, 2014)
Extracorporeal photopheresis (ECP) has been used as a component of combined immunosuppressive therapy in 53 patients with steroid-refractoryacute “graft-versus-host” disease. Overall response was observed in 35 patients (66 %; 95 % CI 52.6–77.3): complete response (CR) in 15 pts (28.3 %; 95 % CI 18–41.6) and partial response (PR) in 20 pts (37.7 %; 95 % CI 25.9–51.2). 3-year OS was 39 % in patients with clinical response (CR or PR); in the absence of clinical response OS was 8 % during the first year (p < 0.0001). Median methylprednisolone dose before ECP was 2 mg/kg/day, and at the end of ECP course – 0.7 mg/kg/day (p < 0.0001).